Mangrove Seeds and Their Role in Climate Adaptation and Coastal Ecosystem Management - SADR UL ANAM; ABDUL KAREEM VETTAN; POOJA SURESH; JASMIN LAILA RASHEED (Seed Research, 2025)
Mangroves represent specialized coastal ecosystems that play a crucial role in shoreline stabilization, carbon storage, and biodiversity conservation. Their seeds and propagules possess unique physiological and morphological adaptations that enable successful germination and establishment under saline and waterlogged conditions. Understanding these biological traits is essential for developing efficient propagation and restoration strategies. This article examines the seed biology of mangroves, the environmental parameters influencing their germination, and practical approaches for seed handling and establishment. Methods including pre-sowing treatments, nursery techniques, and recent innovations such as drone-assisted dispersal are discussed with reference to their application in the United Arab Emirates. By integrating conventional and advanced propagation methods, the study highlights the importance of mangrove seed-based approaches in enhancing restoration success and contributing to climate-resilient coastal management.